Love of the land: Social-ecological connectivity of rural landholders. (April 2017) - Baldwin, Claudia; Smith, Tanzi; Jacobson, Chris
Abstract: Understanding how landholders relate to the land and water they manage is crucial to sustainable natural resource management policy and practice. This study focuses on the relationship that rural landholders, both producers and rural lifestylers, have with their land and waterways, to provide insight into a social-ecological dynamic that contributes to social resilience. Mixed qualitative methods of semi-structured interviews and photovoice are used to examine stewardship; place attachment and constituent components of affective, functional and cognitive connection; as well as sense of community, through a case study in the Mary River valley in South-east Queensland Australia. Powerful visual images from participant-derived photos illustrate rural landholders' views of the interwined connections of landscapes and communities and their 'love of the land'. The study thus expands the breadth of methods used in investigating place attachment. It contributes to the theoretical understanding of how the integrated nature of stewardship, place and community build and maintain social resilience. Understanding landholder relationships and motivations as part of a social-ecological system can enable better targeting of land management support. Highlights: Rural landholders form strong affective attachment to their own properties. Person-place interaction leads to attachment to place. Reflection on strength of attachment surfaces under threat of loss of place. Attachment is enhanced through learning and understanding the landscape. People-place relationships demonstrate social-ecological systems and reinforce and build social resilience.